Inclusive Training in Fencing as a Means of Changing Attitude to People with Disabilities - Р. Ю. Свічкар; О. А. Димар (OVS LLC, 2015)
Research objective: to develop and improve the training of fencers using inclusive training in order to increase sport results and shape a positive attitude to people with disabilities. Methods. The co-training of the "Unifekht" Sports Club fencers and wheelchair fencers lasted for three months.  The athletes underwent the preliminary and the final testing on the target that showed a number of hits. Besides, during the individual lesson, the coach tested the athlete for the quality of performing attacking and defensive techniques. The preliminary and the final questionnaires revealed the opinions of the coaches, instructors of the Department of Fencing, fencers and wheelchair fencers and the students of the School of Physical Education and Sports of H. S. Skovoroda Kharkiv National Pedagogical University as to the attitude of the athletes of both categories to sports and "Invasport" in Ukraine. There were 40 respondents taking the questionnaires: 3rd-year students (10 people), fencers (10 people), instructors of the Department of Fencing (5 persons), wheelchair fencers (8 people), fencing coaches (5 persons), wheelchair fencing coaches (2 persons). Results. The study shows that, despite the high results of the athletes with disabilities, there exist certain problems in Ukraine that affect the willingness of people with disabilities to go in for sports. The main causes thereof are the low level of financial support and the low quality of medical care. By the research results, the respondents indicate the main criterion motivating people with special needs to do wheelchair fencing to be: self-expression and self-realization (68%), an opportunity to communicate (21%), and financial support (11%). The factors of low interest in wheelchair fencing are: lack of motivation to training people with special needs (26%); social policy of the state (23%); poor facilities and resources in the specialized institutions (20% of the respondents). At the same time, 60% of the respondents without health defects are willing to assist in holding various sports events; 30% will agree to assist if they are not otherwise engaged (work, studying, personal circumstances). The results of the questionnaires and the testing of the fencers' technical abilities prove co-training to be effective for the athletes of both categories.